The current role of the artificial urinary sphincter in male and female urinary incontinence - Ab Rashid, Islah Munjih; Cho, Sun Yong; Son, Hwancheol (Korean Society for Sexual Medicine and Andrology, 2013)
The evolution of the artificial urinary sphincter has affected the current surgical options for urinary incontinence. With its unique features, the artificial urinary sphincter (AUS) has been an attractive option for the treatment of urinary incontinence regardless of gender. The current paper discusses the indications, contraindications, types of devices, surgical approaches, outcomes, and complications of the AUS in the treatment of both male and female urinary incontinence. A PubMed review of the available literature was performed and articles reporting implantation of artificial urinary sphincters for urinary incontinence in both male and female patients were evaluated. There was a comparable satisfactory continence rate after the implantation of an AUS (59∼ 97% in males vs. 60∼92% in females). In comparison, there were some differences in the indications, contraindications, surgical approaches, outcomes, and complications of the AUS implanted for urinary incontinence in male and female patients. AUS implantation is a safe and effective surgical option for the treatment of urinary incontinence of various etiologies. Continuous evolution of the device has made it an attractive option for the treatment of both male and female urinary incontinence.